Role of mitomycin-C in endoscopic dacryocystorhinostomy with lacrimal sac stenting - Singh, Jogeshwar; Munjal, Manish; Puri, Sanjeev; Chopra, Parth; Munjal, Shubham; Garg, Akshi; Chopra, Hemant; Garg, Dinesh (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2020)
Background: This study critically evaluates the effectiveness of mitomycin-C in conventional endoscopic dacryocystorhinostomy (ENDODCR) that minimizes the reclosure of a neo-ostium by retaining an enlarged marsupialized lacrimal sac. Methods: The combined retrospective and prospective study included 24 patients in the study group, who underwent endoscopic dacryocystorhinostomy in the Department of Otorhinolaryngology and Ophthalmology in a period of 1.5 years (June 2006 to January 2008). Results: An 83.33% primary success rate was observed, without any serious complications. Obstruction of the neo-ostium with granulation tissue was observed in 20.83% cases. Overall, the success rate of group I was 91.67% as compared to 75% in group II. Conclusions: Intra operative mitomycin-C application is effective in increasing the success rate of DCR surgery in standard nasolacrimal duct obstruction, and no significant complications resulted from its use.